(3TQM YeOI Cgd GdJhajb hGdJSOjO aj TQM YbjOI Cgd GdJhMjOs - (3GdSfhSj, eMeO Hf jhSa Hf GdMSjf, J (B895 (3g`s ((3GdbSWfWjfjIs)
(3ChdgG (B:s
(3HYO GdHSedI ; bGd CHh YHO Gddg eMeO Hf jhSa GdSfhSj GdMSfj GdeGdcj GdMeO ddg GdhGSY GdLhO hHYO aCge eG jTZd Hg GdYGbd YbGFO Yde GdJhMjO Ef habfG Gddg SHMGfg dhVY YbjOI UZjQI eMJhjI Ydi LejY YbGFO GdJhMjO HTQM dgG eNJUQs
(3BNQgG (B:s
(3ef GdahGFO CTQJ Hbhdj ajCUd GdYbjOI jQi dgG ef GdCSQGQ hGdYLGjH Ef TGA Gddg JYGdi eG dG jONd JMJ MUQ hgPG GdaUd GdQGHY gh BNQ GdaUhd GdSHYI GdeJYdbI HcdeI GdJhMjOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 154s
(3eYLe GdeDdajf (B3 / 781s
(3cTa GdXfhf (B2 / 1158s
(3eYLe GdeWHhYGJ (B1058s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds